Transactions cost theory influence in strategy research: a review through a bibliometric study in leading journals - Martins, Rodrigo (2021)
Transaction cost theory (TCT) is widely used in several management disciplines. Its value for explaining organizational phenomena and managers’ decisions is well accepted and has been recognized with two Nobel laureates (Ronald Coase and Oliver Williamson). In this paper we examine the impact of TCT on extant research in top tier management journals. We conduct a bibliometric study of citations and co-citations to uncover the connections between authors and presumably theories. We conclude that TCT, albeit its specific focus on the transactions as the unit of analysis, is present in the majority of management- and business-related research.